EVALUASI KELENGKAPAN PENGISIAN DOKUMEN REKAM MEDIS INSTALASI RAWAT INAP DENGAN PENDEKATAN ANALISA KUALITATIF DAN KUANTITATIF DI RSIA KENDANGSARI MERR SURABAYA - Linda Handayuni (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
Based on the initial survey results indicate that the activity has not done well assembling proven medical records of 10 documents were taken at random showed as much as 34% incomplete and as much as 7% inconsistent. The research purposed to identify the completeness general consent, sign out sheet, initial assessment, and consistency of the general data of patients RSIA Kendangsari Merr Surabaya. This type of research is descriptive using retrospective study which collects data to look back on the causes or variables that influence a result. Conducted in April-July 2016. The sampling technique used purposive non-random sampling, on January until March 2016.The results showed the general consent highest data on incomplete answers is authentication patient / family / responsible (18%), on a sheet in and out of the highest incomplete is the date of authentication (74%), on a prior assessment of the highest data on the answer is incomplete is pain, and the last drug (100%). In the stuffing consistency shows name, date of birth, age, and gender shows the results as a whole (100%) is consistent. So the need to increase awareness and discipline officers assembling in equipping medical records, training, socialization, charging SPO manufacture of medical records